Large left paraduodenal hernia identified and repaired by laparoscopy: A case report. Issue 4 (April 2023) - Xue, Yingming; Liu, Chao; Lin, Bin; Ding, Pengcheng; Qi, Hong
Paraduodenal hernias (PDHs) are rare types of internal hernias that pose a significant diagnostic and therapeutic challenge because they can present with non-specific symptoms ranging from digestive disorders and chronic abdominal pain to symptoms of intestinal obstruction which may be life-threatening. We describe here a woman in her early 30's who presented to the emergency department with a three-hour history of generalized intermittent crampy abdominal pain. She had experienced multiple similar episodes of this pain over the past 20 years. Totally laparoscopic technique was used to complete the diagnosis and treatment of a large left PHD with accompanying acute intestinal obstruction. The operation was successful and the patient was discharged from hospital 10 days later. PDH should be considered if a patient complains of recurrent abdominal pain without any other obvious explanation; a laparoscopic approach can be used to identify and repair the hernia.